2016
DOI: 10.1371/journal.pone.0167660
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review and Meta-Analysis of a Measure of Staff/Child Interaction Quality (the Classroom Assessment Scoring System) in Early Childhood Education and Care Settings and Child Outcomes

Abstract: The quality of staff/child interactions as measured by the Classroom Assessment Scoring System (CLASS) in Early Childhood Education and Care (ECEC) programs is thought to be important for children’s outcomes. The CLASS is made of three domains that assess Emotional Support, Classroom Organization and Instructional Support. It is a relatively new measure that is being used increasingly for research, quality monitoring/accountability and other applied purposes. Our objective was to evaluate the association betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
87
2
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(103 citation statements)
references
References 53 publications
9
87
2
5
Order By: Relevance
“…Two quality indicators have been discussed and studied as key to explaining how regular center‐based provision relates to child outcomes: global and domain‐specific process quality (Halle, Vick Whittaker, & Anderson, ; Kluczniok & Roßbach, ). Despite numerous studies and reviews on effects of process quality, only a few meta‐analyses have been conducted with less conclusive findings (Brunsek et al, ; Burchinal, Kainz, & Cai, ; Burchinal, Zaslow, & Tarullo, ; Keys et al, ; Perlman et al, ). Moreover, these meta‐analyses focused on evidence from the United States.…”
Section: Conceptualization and Measurement Of Process Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“…Two quality indicators have been discussed and studied as key to explaining how regular center‐based provision relates to child outcomes: global and domain‐specific process quality (Halle, Vick Whittaker, & Anderson, ; Kluczniok & Roßbach, ). Despite numerous studies and reviews on effects of process quality, only a few meta‐analyses have been conducted with less conclusive findings (Brunsek et al, ; Burchinal, Kainz, & Cai, ; Burchinal, Zaslow, & Tarullo, ; Keys et al, ; Perlman et al, ). Moreover, these meta‐analyses focused on evidence from the United States.…”
Section: Conceptualization and Measurement Of Process Qualitymentioning
confidence: 99%
“…Interestingly, the effects of the ECERS‐R were superimposed by effects of the more interaction‐specific CLASS subscale or domain‐specific measures, yet again analyzed separately for the included studies. Perlman et al (), however, report no significant overall effect for the CLASS in a meta‐analysis of U.S. studies; and Brunsek et al () observed a significant effect for the ECERS‐R only for language but not math outcomes. In contrast to other meta‐analyses both did not consider children’s individual characteristics and family background in their analyses, which seems important given that children from disadvantaged backgrounds are overrepresented in most of the U.S. studies.…”
Section: Conceptualization and Measurement Of Process Qualitymentioning
confidence: 99%
“…It is notoriously challenging to measure quality in ECE settings in ways that are systematically and strongly related to children's learning gains (Burchinal, ). Still, existing research suggests that, although they are costlier to collect, measures of process quality (e.g., the Classroom Assessment Scoring System [CLASS]), are more consistent, though modest, predictors of children's learning than are structural measures (Araujo et al., ; Hamre & Pianta, ; Howes et al., ; Mashburn et al., ; Perlman et al., ; Sabol et al., ).…”
Section: Accountability In Early Childhood Educationmentioning
confidence: 99%
“…It is notoriously challenging to measure quality in ECE settings in ways that are systematically and strongly related to children's learning gains (Burchinal, 2018). Still, existing research suggests that, although they are costlier to collect, measures of process quality (e.g., the Classroom Assessment Scoring System [CLASS]), are more consistent, though modest, predictors of children's learning than are structural measures (Araujo et al, 2016;Hamre & Pianta, 2005;Howes et al, 2008;Mashburn et al, 2008;Perlman et al, 2016;Sabol et al, 2013).…”
Section: Accountability In Early Childhood Educationmentioning
confidence: 99%